Emulsions stabilized by cellulose-based nanoparticles for curcumin encapsulations: In vitro antioxidant properties - Jian Zhang; Huien Zhang; Liping Liu; Zhongfa Chen (Frontiers in Nutrition, 2022)
To improve the dispersity and antioxidant properties of curcumin, curcumin emulsions covered with cellulose particles (CP) with different structures were successfully prepared, and the structural characteristics, stability, and antioxidant properties of emulsions were investigated. The results showed that the CP obtained by increasing the hydrolysis time had smaller particle size, better water dispersion, and interfacial adsorption capacity. The encapsulation efficiency of curcumin in emulsion stabilized by cellulose particle hydrolyzed for 10 h can reach about 80%. After 9 days, all emulsions showed good stability, and no obvious creamed layer was observed. Compared to cellulose particles hydrolyzed for 2 h (CP2), emulsions stabilized by cellulose particles hydrolyzed for 6 h (CP6) and 10 h (CP10) exhibited better stability and free fatty acid (FFA) release. Meanwhile, the DPPH scavenging activity of curcumin emulsion stabilized by CP significantly increased with increasing the hydrolysis time and was much higher than that of pure emulsion and curcumin/water due to the higher solubility (1,455 times compared with curcumin/water solution) of curcumin, and these results could provide useful data for the stability and encapsulation of curcumin.